Construction of a Humanized PBMC-PDX Model to Study the Efficacy of a Bacterial Marker in Lung Cancer Immunotherapy. (28th August 2022) - Wu, Chengwei; Wang, Xinning; Shang, Haitao; Wei, Hong
Abstract : Commensal microbiome is a key factor of lung cancer immunotherapy efficacy. Elucidating the role of specific strains as bacterial markers in immunotherapy has drawn great attention from the academia. At present, most preclinical studies about the relationship between bacterial markers and immunotherapy rely on the syngeneic mouse models. However, mice differ greatly from humans in immune system and tumor characteristics. In this study, humanized mouse models based on peripheral blood mononuclear cells (PBMCs) immune reconstitution and lung cancer cell line-derived xenograft (CDX) or patient-derived xenograft (PDX) were constructed. The PBMC-PDX model was shown to be superior to the PBMC-CDX model in preserving tumor heterogeneity and construction time-saving. Through optimizing the experimental process, the time it took for humanized models to evaluate the effect of cancer treatment was reduced to 42 days. Next, by utilizing PBMC-PDX mice treated with antibiotics (ATB), the role of Bifidobacterium longum in lung cancer immunotherapy was studied. It was found that although both Bifidobacterium longum and immunotherapy drug pembrolizumab alone showed suppressing tumor growth, the efficacy of pembrolizumab was attenuated when administrated to mice colonized with Bifidobacterium longum . Further exploration revealed that Bifidobacterium longum caused significant changes in the proportion of human CD45 + cells in the PBMC-PDX model. The PBMC-PDX model has the potential to be applied as an efficient platform to support evaluation of bacterial markers in immunotherapy research and facilitate development of precision medicine targeting human commensal bacteria.